2022
DOI: 10.1111/btp.13118
|View full text |Cite
|
Sign up to set email alerts
|

Open habitats in a tropical biodiversity hotspot support pollinator diversity in both protected and unprotected areas

Abstract: The biosphere is changing rapidly (Ellis et al., 2010) through anthropogenic activities that result in fragmentation and loss of natural habitats Harrison et al., 2017). These changes cause increasing threats to biodiversity, especially among species with ecological interactions such as pollinators, influencing the delivery of ecosystem services necessary for the maintenance of both natural and agricultural ecosystems (Brittain et al., 2013;CBD, 2018; IPBES, 2016). Anthropogenic factors such as habitat fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Consequently, we do not recognize that the unprotected matrix may serve as source or destination locations for species undergoing climate-induced range shifts in and out of protected areas, respectively. Although this could be an important consideration in regions with fairly low land use intensities (e.g., Balogun et al, 2022), this is not always the case when protected areas are concentrated in particular landforms (e.g., mountains; Figure 6). Ultimately, future studies could better incorporate the unprotected matrix by, for example, including lands with low land-use intensities (cf.…”
Section: Ta B L E 1 Percent Of Terrestrialmentioning
confidence: 99%
“…Consequently, we do not recognize that the unprotected matrix may serve as source or destination locations for species undergoing climate-induced range shifts in and out of protected areas, respectively. Although this could be an important consideration in regions with fairly low land use intensities (e.g., Balogun et al, 2022), this is not always the case when protected areas are concentrated in particular landforms (e.g., mountains; Figure 6). Ultimately, future studies could better incorporate the unprotected matrix by, for example, including lands with low land-use intensities (cf.…”
Section: Ta B L E 1 Percent Of Terrestrialmentioning
confidence: 99%
“…In Serbia, one of the main hotspots of hoverfly (Syrphidae) diversity in Europe, PAs are only partly efficient in the conservation of this family of pollinating insects [40]. A recent study [41] assessing insect pollinator diversity in protected vs. unprotected areas in a hotspot of biodiversity in Nigeria found that pollinator diversity varied more in relation to land-use type rather than area protection per se.…”
Section: Introductionmentioning
confidence: 99%